Therapy of hypertension in special clinical conditions – metabolic syndrome - Gaciong, Zbigniew; Lewandowski, Jacek (Przewodnik Lekarza/Guide for GPs, 2010)
Hypertension is most prevalent risk factor for cardiovascular diseases which afflicts more than one third of adult world population. Hypertension frequently coexists with metabolic syndrome which prevalence is estimated on about 20%. According to definition, however not universally adopted, the diagnosis of metabolic syndrome is based on presence of at least 3 of listed abnormalities: increased waist circumference, low plasma HDL concentration, high concentration of triglicerides and glucose and/or high blood pressure. It was shown that cardiovascular morbidity and mortality as well as the risk of developing diabetes are markedly higher in individuals with the syndrome than those without it. Therapeutic approach to the syndrome is complex. In all individuals with metabolic syndrome, intense lifestyle changes including reduction in body weight by low caloric diet and physical exercise should be adopted. Pharmacological therapy when there is a hypertension should start with a drug unlikely to facilitate onset of diabetes. Therefore blockers of the renin-angiotensin system ie ACE inhibitors or sartans should be used followed by the addition of a calcium antagonist or thiazide-like diuretic. Additional administration of antidiabetic or lipid lowering drugs is frequently required. However, the optimal blood pressure values to achieve in patients with metabolic syndrome have never been investigated thus it appears reasonable to bring blood pressure to the normal range i.e. below 140/90 mm Hg.